A novel two-stage process for the effective treatment of swine wastewater using Chlorella sorokiniana AK-1 based algal-bacterial consortium under semi-continuous operation. (December 2022) - Chen, Chun-Yen; Kuan, Shu-Ping; Nagarajan, Dillirani; Chen, Jih-Heng; Ariyadasa, Thilini U.; Chang, Jo-Shu
Graphical abstract: Highlights: C. sorokiniana AK-1 can form a stable consortium with wastewater-derived bacteria. Small microalgal inoculum size was sufficient to promote growth in the presence of bacteria. Semi-batch mode attained higher biomass and nutrient removal. A novel two-stage process with an initial bacteria-only startup phase is employed. The effluent of full-strength wastewater treatment met the discharge standards of Taiwan. Abstract: This study aimed at developing an eco-friendly and effective treatment for swine wastewater (SWW) using a designer microalgae-bacteria consortium. A functional algal bacterial consortium was developed with SWW-derived bacteria and Chlorella sorokiniana AK-1. Light intensity (300 µmol/m 2 /s) and inoculum size (0.15 and 0.2 g/L for microalgae and bacteria) were optimized. Semi-batch operation treating 50 % SWW resulted in a COD, BOD, TN, and TP removal efficiency of 81.1 ± 0.9 %, 97.0 ± 0.7 %, 90.6 ± 1.6 % and 91.3 ± 1.1 %, respectively. A novel two-stage process with an initial bacterial start-up stage followed by microalgal inoculation was applied for attaining stable organic carbon removal, in addition to satisfactory TN and TP removal. Full strength SWW was treated with this strategy with COD, BOD, TN, and TP removal efficiencies of 72.1 %, 94.9 %, 88 %, and 94.6 %, respectively. The biomass consisted of 36 % carbohydrates, indicating a potential feedstock for biochar production. In addition, the effluent met the standards for effluent discharge in Taiwan.